Polyolefin composition as well as preparation method and application thereof

By adding polyamide materials, plant fibers and polymer graft polar monomers to the polyolefin resin, the problem of poor adhesive properties of polyolefin materials is solved, and a polyolefin composition with high surface polarity and good adhesive properties is achieved, which is suitable for a variety of industrial applications.

CN119752047APending Publication Date: 2025-04-04WUHAN JINFA TECH CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411987080.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Traditional polyolefin materials have limitations in their bonding properties, especially their low surface energy, poor adhesion to other materials, and high flame treatment and plasma treatment costs and it is difficult to uniformly handle complex-shaped products.

Method used

By adding polyamide material, specific plant fibers and polymer graft polar monomers to the polyolefin resin, the surface polarity and adhesion properties of the material are synergistically improved, while reducing the linear thermal expansion coefficient and improving dimensional stability.

Benefits of technology

The polyolefin composition has achieved high surface polarity, good adhesive properties without flame treatment and plasma treatment, and has good dimensional stability, and is suitable for a variety of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222836920000011
    Figure BDA0005222836920000011
  • Figure BDA0005222836920000081
    Figure BDA0005222836920000081
  • Figure BDA0005222836920000082
    Figure BDA0005222836920000082
Patent Text Reader

Abstract

The invention discloses a polyolefin composition as well as a preparation method and application thereof, and belongs to the field of high polymer materials. According to the polyolefin composition disclosed by the invention, the polyamide material, the plant fiber and the polymer grafted polar monomer with specific addition amounts are added to synergistically improve the surface polarity, the adhesive property and the dimensional stability of the polyolefin composition, so that the polyolefin composition is high in surface polarity and has good adhesive property without flame treatment and plasma treatment; and meanwhile, the adhesive has good dimensional stability and is suitable for the field of adhesive bonding and coating, such as the packaging industry, the wood-plastic floor industry, the automobile industry and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polymer materials, and in particular to a polyolefin composition and a preparation method and application thereof. Background Art

[0002] Polyolefin materials have been widely used in many fields due to their good chemical stability, corrosion resistance, electrical insulation and processing performance. For example, in the automotive industry, polyolefins are used to manufacture interior parts, bumpers, etc.; in the field of building materials, they can be used to make wood-plastic flooring, etc.; in the packaging industry, they are a common choice of packaging materials.

[0003] Traditional polyolefin materials have certain limitations in terms of bonding performance. Generally, polyolefin has low surface energy and poor bonding with other materials. Currently, flame treatment or plasma treatment is often used to improve the bonding strength between polyolefin and other materials (such as films, rubbers, coatings, etc.), but these treatments not only require special equipment and processes, increasing production costs, but also may be difficult to achieve uniform treatment effects for some complex-shaped products, thus affecting the overall bonding performance.

[0004] Therefore, considering the characteristics of polyolefin materials and a large number of working conditions requiring adhesion, the development of polyolefin composite materials that are flame- and plasma-free, have high surface polarity, are easy to bond, and have good dimensional stability has important technical value and market potential. Summary of the invention

[0005] Based on the defects of the prior art, the purpose of this application is to provide a polyolefin composition and a preparation method and application thereof, aiming to make the surface polarity of the polyolefin composition high, have good bonding properties without flame treatment and plasma treatment, and have good dimensional stability.

[0006] In order to achieve the above objectives, in a first aspect, the present application provides a polyolefin resin comprising the following components in parts by weight:

[0007]

[0008] The plant fibers have an average diameter of ≤160 μm and an average length of ≥1 mm.

[0009] Polyolefin resin is a non-polar material with low surface activity and poor bonding performance. The introduction of polyamide material as a polarity regulator can improve its surface polarity and improve the bonding performance. In addition, polyamide material has good coating properties, which is beneficial to reducing the linear thermal expansion coefficient of the polyolefin substrate and improving its dimensional stability. The above-mentioned plant fiber is a kind of viscosity-increasing filler. Due to its specific average diameter and average length, it has good compatibility with the polyamide material. It not only has a large number of polar groups such as -OH on the surface to enhance the surface polarity of the composite material, but also can form a rough surface of the composite material, which is helpful to improve the bonding performance. In addition, the above-mentioned plant fiber can also reduce the shrinkage rate of the polyolefin substrate, limit the thermal expansion and contraction caused by temperature changes, and achieve a reduction in the linear thermal expansion coefficient. The polymer grafted polar monomer, on the one hand, as a compatibilizer, helps to improve the interface compatibility between the polyamide material and the polyolefin substrate, make the two-phase structure distribution more uniform, and achieve a more uniform and stable high polarity. On the other hand, it contains polar groups, which can further improve the polarity of the material and improve the bonding performance.

[0010] The polyolefin composition has high surface polarity under the synergistic effect of specific added amounts of polyamide materials, specific plant fibers, and polymer grafted polar monomers, and has good bonding properties without flame treatment and plasma treatment. At the same time, it has a low linear thermal expansion coefficient, which can prevent the material from changing in size due to temperature changes after bonding, thereby damaging the bonding surface and reducing the bonding strength.

[0011] The polyolefin resin is 29 to 95 parts by weight, such as 29 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 60 parts by weight, 70 parts by weight, 80 parts by weight, 90 parts by weight, 95 parts by weight or any two parts thereof. Preferably, the polyolefin resin is 49 to 86 parts by weight, which can obtain higher dyne value and bonding strength, as well as lower linear thermal expansion coefficient at a lower price, and has a higher cost performance.

[0012] The polyamide material is 5 to 40 parts by weight, such as 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight or an interval formed by any two of the above values.

[0013] The polymer grafted polar monomer is 0.5 to 20 parts by weight, such as 0.5 parts by weight, 1 part by weight, 3 parts by weight, 5 parts by weight, 7 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight, 17 parts by weight, 20 parts by weight or an interval formed by any two of the above values.

[0014] The plant fiber is 1 to 20 parts by weight, such as 1 part by weight, 1 part by weight, 3 parts by weight, 5 parts by weight, 7 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight, 17 parts by weight, 20 parts by weight or an interval formed by any two of the above values.

[0015] Preferably, the weight ratio of the polyamide material to the plant fiber is (0.4-14): 1. For example, the weight ratio of the polyamide material to the plant fiber is 0.4:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1 or an interval formed by any two of the above values.

[0016] More preferably, the weight ratio of the polyamide material to the plant fiber is (0.9-2.6):1.

[0017] When the weight ratio of the polyamide material to the plant fiber is in the range of (0.4-14):1, especially in the range of (0.9-2.6):1, the surface polarity, adhesive properties and dimensional stability of the polyolefin composition are better balanced.

[0018] The average diameter of the plant fiber is ≤160μm, and the average length is ≥1mm. For example, the average diameter of the plant fiber is 160μm, 140μm, 120μm, 100μm, 80μm, 60μm, 40μm, 30μm, 20μm, 10μm, 5μm, 3μm, or an interval formed by any two of the above values; the average length of the plant fiber is 1mm, 5mm, 7mm, 10mm, 12mm, or an interval formed by any two of the above values.

[0019] Preferably, the plant fibers have an average diameter of 12 to 45 mm and an average length of 1 to 12 mm.

[0020] Considering that the smaller the average diameter of the plant fiber, the better the compatibility with the substrate polyolefin / PA, the more conducive to viscosity increase, but the average diameter is too small to be easy to prepare, the average diameter of the plant fiber is preferably 12 to 45 mm to make it more cost-effective.

[0021] The average diameter and average length of the plant fibers are detected by a two-dimensional measurement method, which is as follows: 200 plant fibers are randomly selected, their diameters and lengths are counted respectively, and then the average value is calculated, which is the plant fiber of this time.

[0022] Preferably, the plant fiber is obtained by soaking the plant fiber in an alkali solution, washing it with water and subjecting it to a steam explosion treatment.

[0023] Preferably, the alkali content in the alkali solution is 0.5-10 wt %. The alkali in the alkali solution can be selected from at least one of sodium hydroxide and potassium hydroxide.

[0024] Preferably, the soaking temperature is 10-90° C., and the soaking time is 0.5-24 h.

[0025] Preferably, the steam explosion is performed 1 to 3 times, and the pressure of each steam explosion is 0.5 to 10 MPa.

[0026] Preferably, a drying process is performed after the water washing and between the steam explosion. Preferably, the moisture content of the plant fiber after the drying process is 10% to 50%. The temperature of the drying process is preferably 40 to 80°C.

[0027] Preferably, the plant fiber includes at least one of hemp fiber, wood fiber, and bamboo fiber. More preferably, the plant fiber includes hemp fiber. Compared with plant fibers such as wood fiber and bamboo fiber, hemp fiber is easier to obtain a smaller diameter and has good fiber retention.

[0028] Preferably, the relative viscosity of the aliphatic polyamide material is ≤2.8. More preferably, the relative viscosity of the aliphatic polyamide material is 2.0-2.8.

[0029] The relative viscosity of the aliphatic polyamide material is ≤2.8, such as 2.8, 2.7, 2.6, 2.5, 2.4, 2.3, 2.2, 2.1, 2.0 or the interval formed by any two of the above values, the material has good processing performance. Preferably, the relative viscosity of the aliphatic polyamide material is 2.0-2.8, which is conducive to the dispersion of plant fibers and helps the plant fibers maintain a higher retention length.

[0030] The relative viscosity of the aliphatic polyamide material can be measured by the sulfuric acid solvent method in ISO 307-2007 standard, and the mass fraction of sulfuric acid in the sulfuric acid solvent used is 98%.

[0031] Preferably, the aliphatic polyamide material includes at least one of PA6, PA11 and PA12.

[0032] Preferably, in the polymer-grafted polar monomer, the polymer includes at least one of polyethylene, polypropylene, ethylene-octene copolymer, ethylene-vinyl acetate copolymer or ethylene-ethyl acrylate copolymer, and the polar monomer includes at least one of maleic anhydride or its derivatives.

[0033] Preferably, the melt index of the polymer grafted polar monomer at 190° C. and 2.16 kg load is 0.5 to 200 g / 10 min, and the grafting rate of the polar monomer is 0.5 wt.% to 2.0 wt.%. For example, the melt index of the polymer grafted polar monomer at 190° C. and 2.16 kg load is 0.5 g / 10 min, 1 g / 10 min, 5 g / 10 min, 10 g / 10 min, 20 g / 10 min, 30 g / 10 min, 40 g / 10 min, 50 g / 10 min, 60 g / 10 min, 70 g / 10 min, 80 g / 10 min, 90 g / 10 min, 100 g / 10 min, 110 g / 10 min, 120 g / 10 min , 130g / 10min, 140g / 10min, 150g / 10min, 160g / 10min, 170g / 10min, 180g / 10min, 190g / 10min, 200g / 10min or an interval formed by any two of the above values; the grafting rate of the polar monomer is 0.5wt.%, 0.7wt.%, 1.0wt.%, 1.2wt.%, 1.5wt.%, 1.7wt.%, 2.0wt.% or an interval formed by any two of the above values.

[0034] The melt index of the polymer grafted polar monomer is measured according to ASTM D1238-13, and the grafting rate of the polar monomer is determined as follows: the grafted material is placed in a NaOH solution and heated to completely neutralize the polar monomer (maleic anhydride or its derivatives), and then the excess NaOH is titrated out with an HCl solution, thereby calculating the grafting rate of the polar monomer.

[0035] Preferably, the polyamide material comprises an aliphatic polyamide material, which has a low melting point and is easy to process.

[0036] Preferably, the polyolefin resin includes at least one of high-density polyethylene, low-density polyethylene, linear low-density polyethylene or polypropylene.

[0037] Preferably, the melt index of the high-density polyethylene at 190°C and a load of 2.16 kg is 0.1 to 20 g / 10 min. For example, the melt index of the high-density polyethylene at 190°C and a load of 2.16 kg is 0.1 g / 10 min, 0.5 g / 10 min, 1 g / 10 min, 5 g / 10 min, 10 g / 10 min, 20 g / 10 min, or an interval formed by any two of the above values.

[0038] Preferably, the melt index of the low-density polyethylene at 190° C. and 2.16 kg load is 0.1 to 80 g / 10 min. For example, the melt index of the low-density polyethylene at 190° C. and 2.16 kg load is 0.1 g / 10 min, 0.5 g / 10 min, 1 g / 10 min, 5 g / 10 min, 10 g / 10 min, 20 g / 10 min, 30 g / 10 min, 40 g / 10 min, 50 g / 10 min, 60 g / 10 min, 70 g / 10 min, 80 g / 10 min or an interval formed by any two of the above values.

[0039] Preferably, the melt index of the linear low-density polyethylene at 190°C and a load of 2.16 kg is 1 to 20 g / 10 min. For example, the melt index of the linear low-density polyethylene at 190°C and a load of 2.16 kg is 1 g / 10 min, 3 g / 10 min, 5 g / 10 min, 7 g / 10 min, 10 g / 10 min, 12 g / 10 min, 15 g / 10 min, 17 g / 10 min, 20 g / 10 min, or an interval formed by any two of the above values.

[0040] Preferably, the polypropylene (i.e., the polypropylene in the polyolefin resin) has a melt index of 1 to 100 g / 10 min at 230° C. and a load of 2.16 kg. For example, the melt index of the polypropylene in the polyolefin resin at 230° C. and a load of 2.16 kg is 1 g / 10 min, 5 g / 10 min, 10 g / 10 min, 20 g / 10 min, 30 g / 10 min, 40 g / 10 min, 50 g / 10 min, 60 g / 10 min, 70 g / 10 min, 80 g / 10 min, 90 g / 10 min, 100 g / 10 min, or an interval formed by any two of the above values.

[0041] The melt indexes of the high-density polyethylene, the low-density polyethylene, the linear low-density polyethylene, the polyolefin resin, and the polypropylene (ie, the polypropylene in the polyolefin resin) are measured according to ASTM D1238-13.

[0042] Preferably, the polypropylene (ie the polypropylene in the polyolefin resin) includes at least one of homopolypropylene and copolymer polypropylene.

[0043] Preferably, the polyolefin composition further comprises the following components by weight: 0.1-1 part of antioxidant and 0.1-1 part of lubricant.

[0044] Preferably, the antioxidant includes at least one of a phenolic antioxidant, a phosphite antioxidant, a divalent sulfur antioxidant, and a hindered amine antioxidant.

[0045] Preferably, the lubricant includes at least one of an amide lubricant, a metal soap lubricant, and a low molecular ester lubricant, wherein the low molecular ester lubricant refers to a lower alcohol ester formed by a fatty acid, and the carbon number of the fatty acid generally does not exceed 20.

[0046] Preferably, the weight percentage of the polyolefin resin in the polyolefin composition is above 38%, such as 40%, 50%, 60%, 70%, 80%, 90%, 92% or an interval formed by any two of the above values.

[0047] In a second aspect, the present application provides a method for preparing the polyolefin resin, comprising the following steps: mixing all component raw materials, melt-extruding, granulating, and drying to obtain a polyolefin composition.

[0048] Preferably, the melt extrusion is carried out in a twin-screw extruder. The aspect ratio of the twin-screw extruder is preferably (36-48): 1. The temperature of each zone of the twin-screw extruder is preferably set as follows: 80-120°C in zone 1, 180-200°C in zones 2-5, and 200-210°C in zones 6-8.

[0049] In a third aspect, the present application provides the use of the polyolefin composition for preparing household items, electronic components, household appliances, gardening equipment, medical technology equipment, motor vehicle parts and body parts. In particular, the above-mentioned polyolefin composition can be used to prepare parts with high surface polarity, good bonding performance and good dimensional stability. The plastic parts made of the polyolefin composition do not need to be flame treated and plasma treated, that is, when using an adhesive (such as PUR hot melt polyurethane adhesive) to bond with other materials (such as films, rubbers, coatings, etc.), they are easy to bond, have high bonding strength, and have good dimensional stability of the bonded products.

[0050] In a fourth aspect, the present application provides a product made of the polyolefin composition, wherein an adhesive is provided on the surface of the product.

[0051] Compared with the prior art, the beneficial effects of this application are:

[0052] (1) The polyolefin composition of the present application adds a specific amount of polyamide material, specific plant fiber and polymer grafted polar monomer to utilize these three to synergistically improve the surface polarity, bonding performance and dimensional stability of the material.

[0053] (2) The polyolefin composition of the present application has high surface polarity and has good bonding properties without flame treatment and plasma treatment. It also has good dimensional stability and is suitable for adhesive bonding and coating fields, such as the packaging industry, wood plastic flooring, and the automotive industry. DETAILED DESCRIPTION

[0054] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.

[0055] The raw material information used is as follows. Unless otherwise specified, they are all commercially available raw materials. In addition, the component raw materials used in each parallel experiment are the same:

[0056] Polyolefin resin 1: copolymer PP, melt index at 230℃ / 2.16kg is 9g / 10min, model EP300M, manufacturer CNOOC Shell;

[0057] Polyolefin resin 2: HDPE, melt index at 190℃ / 2.16kg is 8g / 10min, model DMDA-8008, manufacturer Dushanzi Petrochemical;

[0058] Polyamide material 1: PA6, relative viscosity 2.5, model HY-2500A, manufacturer Haiyang Chemical Fiber;

[0059] Polyamide material 2: PA11, relative viscosity 2.3, model BMNO F15, manufacturer Arkema;

[0060] Polyamide material 3: PA12, relative viscosity 2.0, model L20G, manufacturer: Emmans, Switzerland;

[0061] Compatibilizer 1: Polyethylene grafted maleic anhydride, model AMPLIFY TY 1352, manufacturer Dow;

[0062] Compatibilizer 2: Polypropylene grafted maleic anhydride, model PC-3, manufacturer Nanhai Bochen Polymer Materials;

[0063] Compatibilizer 3: Ethylene-octene copolymer grafted with maleic anhydride, model PC-28, manufacturer Nanhai Bochen Polymer Materials;

[0064] Compatibilizer 4: ethylene-vinyl acetate copolymer grafted with maleic anhydride, model C250, manufacturer Dow;

[0065] Compatibilizer 5: Ethylene-ethyl acrylate copolymer grafted with maleic anhydride, model LOTADER 4700, manufacturer SK, South Korea;

[0066] Plant fiber 1: having an average diameter of 12 μm and an average length of 10 mm, and the preparation method thereof is as follows: a commercially available plant fiber--a bundle of ramie long fibers having an average diameter of 200 μm--is uniformly cut into short fibers of 15 mm in length, and then immersed in a 2 wt % NaOH solution at 25° C. for 8 h, washed with clean water to remove residual NaOH, and then dried at 60° C. to a moisture content of 30%, and then added to the hopper of a steam explosion machine for dispersed steam explosion treatment, the number of steam explosions is 3 times, and the steam explosion pressure is 10 MPa each time, and then washed with clean water again, and then dried at 90° C. for 24 h;

[0067] Plant fiber 2: The average diameter is 15 μm, and the average length is 11 mm. The difference between its preparation method and that of plant fiber 1 is that the steam explosion pressure is 5 MPa.

[0068] Plant fiber 3: The average diameter is 40 μm, and the average length is 11.5 mm. The difference between its preparation method and that of plant fiber 1 is that the steam explosion pressure is 2 MPa.

[0069] Plant fiber 4: average diameter is 135 μm, average length is 5 mm, and its preparation method is different from that of plant fiber 1 in that the number of steam explosions is 2, and the plant fiber raw material used is bamboo fiber;

[0070] Plant fiber 5: average diameter 160 μm, average length 1 mm. The difference between its preparation method and that of plant fiber 1 is that the steam explosion times is 1, and the plant fiber raw material used is wood fiber with an average diameter of 350 μm, which is cut into short fibers of 5 mm in length before soaking;

[0071] Plant fiber 6: average diameter 170 μm, average length 10 mm, the preparation method is as follows: commercially available plant fiber with an average diameter of 200 μm - bundled ramie long fibers are evenly cut into 10 mm long short fibers, then immersed in 2wt% NaOH solution at 25°C for 8 hours, washed with clean water to remove residual NaOH, and then dried at 90°C for 24 hours.

[0072] Plant fiber 7: having an average diameter of 200 μm and an average length of 10 mm, the preparation method thereof is as follows: a commercially available plant fiber having an average diameter of 200 μm, namely, a bundle of ramie long fibers, is uniformly cut into short fibers of 10 mm in length, thus obtaining plant fiber 7;

[0073] Antioxidant: Antioxidant 1010, commercially available;

[0074] Lubricant: EBS (N,N-ethylenebisstearamide), commercially available.

[0075] Each of the following examples and comparative examples provides a polyolefin composition, comprising the following steps: mixing all the raw materials, melt extruding, granulating, and drying to obtain the polyolefin composition; wherein the screw length-diameter ratio of the twin-screw extruder is 40:1, and the temperature of each zone of the twin-screw extruder is preferably set as follows: 120°C in zone 1, 220°C in zones 2-4, 235°C in zones 5-6, 225°C in zone 7, and 190°C in zone 8. The formulations of the polyolefin compositions of these examples and comparative examples are shown in Tables 1 and 2.

[0076] The following performance tests were performed on the polyolefin compositions of the above embodiments and comparative examples. The test results are shown in Tables 1 and 2:

[0077] (a) Dyne value test: According to GB / T 14216-2008 standard, the dyne value of the material surface is tested.

[0078] (b) Adhesion strength test: Injection mold a long plastic plate with a length of 200*width 50*thickness 2mm, evenly apply PUR hot melt polyurethane adhesive (TOTASEAL 6023) on the plastic plate within a length of 100mm, then stick a PVC sheet (length 100*width 50*thickness 1mm) on the glue area; bake in a 60℃ oven for 1h, and then let it stand at 25℃ for 24h. Test the tensile peel force, which is the adhesion strength.

[0079] (c) Coefficient of linear thermal expansion (CLTE) test: Injection mold 80*10mm*4mm specimens, then cut 10mm*10mm*4mm, refer to ISO 11359-2-2021, and test the linear expansion coefficient in the range of -40 to 60℃.

[0080] Table 1

[0081]

[0082] Table 2

[0083]

[0084]

[0085] It can be seen from the above data that the compositions of each embodiment have high surface polarity, good bonding performance and good dimensional stability, such as a dyne value of more than 33, a bonding strength of more than 1 N / mm, and a linear thermal expansion coefficient of less than 130 μm / (m·℃).

[0086] Comparison of Examples 2 and 5 to 7 shows that as the amount of polyolefin resin decreases, the dyne value and bonding strength of the composition are higher, and the linear thermal expansion coefficient is lower, but the cost increases. Preferably, the amount of polyolefin resin is 49 to 86 parts by weight to obtain a higher cost-effectiveness.

[0087] From the comparison of Examples 2, 8 to 11, it can be seen that when the weight ratio of PA to plant fiber is too high, the bonding strength and dyne value of the composition are low, and the linear thermal expansion coefficient is high; when the weight ratio of the two is too low, the bonding strength of the composition is low. Therefore, it is preferred that the weight ratio of the two is in the range of (0.4 to 14): 1 to better balance the dyne value, bonding strength and linear thermal expansion coefficient of the material.

[0088] Comparison of Example 4 with Comparative Examples 1 to 4 shows that PA, polymer grafted polar monomers and plant fibers can synergistically improve the surface polarity, bonding performance and dimensional stability of the material, and none of the three can be missing.

[0089] Comparison of Examples 2, 16-19 with Comparative Examples 5-6 shows that the average diameter of the plant fiber must be ≤160 μm to significantly improve the bonding strength of the composition. When the average diameter of the plant fiber is in the range of 12-45 μm, the bonding strength of the composition is higher and the linear thermal expansion coefficient is lower.

[0090] Since no PA, polymer-grafted polar monomer and plant fiber were added to Comparative Example 1, the dyne value and bonding strength were relatively low, and the linear thermal expansion coefficient was relatively high.

[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A polyolefin composition, characterized in that By weight, it includes the following components: The plant fibers have an average diameter of ≤160 μm and an average length of ≥1 mm.

2. The polyolefin composition according to claim 1, characterized in that The polyolefin resin is 49 to 86 parts by weight.

3. The polyolefin composition according to claim 1, characterized in that The weight ratio of the polyamide material to the plant fiber is (0.4-14):1, preferably (0.9-2.6):

1.

4. The polyolefin composition according to claim 1, characterized in that The average diameter of the plant fiber is 12-45 μm, and the average length is 1-12 mm.

5. The polyolefin composition according to claim 1, characterized in that The polyamide material comprises an aliphatic polyamide material, and the relative viscosity of the aliphatic polyamide material is ≤2.8, preferably 2.0-2.

8.

6. The polyolefin composition according to claim 5, characterized in that The aliphatic polyamide material includes at least one of PA6, PA11 and PA12.

7. The polyolefin composition according to claim 1, characterized in that In the polymer-grafted polar monomer, the polymer includes at least one of polyethylene, polypropylene, ethylene-octene copolymer, ethylene-vinyl acetate copolymer or ethylene-ethyl acrylate copolymer, and the polar monomer includes at least one of maleic anhydride or its derivatives.

8. The polyolefin composition according to claim 1, characterized in that At least one of the following conditions is met: (1) The plant fiber is prepared by soaking the plant fiber in an alkali solution, washing it with water and subjecting it to a steam explosion treatment; (2) The plant fiber includes at least one of hemp fiber, wood fiber, and bamboo fiber; (3) the polymer grafted with polar monomer has a melt index of 0.5 to 200 g / 10 min at 190° C. and a load of 2.16 kg, and a grafting rate of the polar monomer is 0.5 wt.% to 2.0 wt.%; (4) the polyolefin resin comprises at least one of high-density polyethylene, low-density polyethylene, linear low-density polyethylene or polypropylene; (5) The following components are also included by weight: 0.1-1 part of antioxidant and 0.1-1 part of lubricant.

9. A method for preparing a polyolefin composition according to any one of claims 1 to 8, characterized in that: The following steps are involved: All the raw materials are mixed, melt-extruded, granulated and dried to obtain a polyolefin composition.

10. A product made of the polyolefin composition according to any one of claims 1 to 8, wherein an adhesive is provided on the surface of the product.

Citation Information

Patent Citations

  • Nylon 6 / polypropylene composite material and preparation method thereof

    CN102850783A

  • Glass fiber reinforced polypropylene / nylon 6 alloy material and preparation method thereof

    CN109776952A

  • Fiber-reinforced resin composition and molded article

    CN116406400A

  • Polyamide / polyolefin composite material as well as preparation method and application thereof

    CN118185299A

  • Polyolefin composition as well as preparation method and application thereof

    CN118290853A